An appraisal of the public secondary school libraries in the first district of Manila - Valderrama, Norma R.; Picache, Ursula G.; Mercado, Filomena C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1970)
Studies the facilities and services of the secondary school libraries in Tondo for the school year 1969-70. Findings with regards to their personnel, collections, quarters, furniture and equipment and finances were presented and analyzed. These were then compared and evaluated against existing standards.
Findings showed that the conditions of the school libraries in general leave much to be desired. Suggestions and recommendations to improve the sad state of these school libraries were made.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: High school libraries -- Philippines -- Tondo, Manila; School libraries (High school) See High school libraries